Strengthening primary health care through e-referral system - Bashar, Md Abu (J Family Med Prim Care, 2019)
Referral is a dynamic process, in which a health worker at one level of the health system, having insufficient resources (drugs, equipment, skills) to manage a clinical condition, seeks the help of a better or differently resourced facility at the same or higher level to assist in. Health care systems of every country are designed in such a way to encourage patients to first attempt to get care at the primary level and then to approach a higher level of care according to the need. This protocol minimizes the costs for the caretaker/patients. However, in most of the countries, patients often bypass primary care facilities and directly go to the higher center thereby, increasing the burden on higher level facilities, the picture is not very different in India also. Health care system in India is plugged by: overpopulation, lack of expert clinicians, skewed distribution of physicians, lack of motivation among existing health care personnel and an ineffective referral mechanism. Due to failure of conventional paper-based referral systems in our country, we can introduce an e-referral system in the era of internet. It is evident from our experiences, that this artificial intelligence enabled e-referral system has many advantages over the traditional paper-based referral system. It will aid health workers for timely management of cases. Most importantly, it will streamline the existing unorganized referral process. Although, for effective e-Referral system, there should be a collaborative platform where easy search and discovery for health care providers is possible and help in decision making. e- Referral should be incorporated in our health system to strengthen it by bridging the access gap may be through Public Private Partnership model.